Voters or consumers : imagining the contemporary electorate - Lilleker, Darren G.; Scullion, Richard (Cambridge Scholars Pub., 2008)
This edited collection seeks to map current thinking and practice in order to assess the extent to which the consumer, as opposed to the voter, should now to be elevated to a central position within our understanding of the relationship between the public and political spheres. The volume will firstly offer an overview of how consumerism has been applied to our understanding of political and voter behaviour so outlining the book's key concepts. The volume then follows a processual approach to ...